Analisis Implementasi Sistem Manajemen Keselamatan Konstruksi (SMKK) (Studi Kasus Pembangunan Gedung Kantor Pengadilan Negeri Sungguminasa Kelas 1a ) - Wudi Darul Putra; Rizki Ayu Saraswati (Departement of Mathematics Education, 2023)
The high number of work accidents in Indonesia, especially in the construction sector, makes the implementation of the Construction Safety Management System (SMKK) very important. Behavior that ignores Occupational Safety and Health (K3) is the biggest contributor to the high number of work accidents, therefore it is deemed necessary to manage OSH systematically and comprehensively in a complete management system as an effort to prevent work accidents. The SMKK assessment in the Renovation and Expansion Project of the Class 1A Sungguminasa District Court office building aims to find out how much the implementation level of the SMKK is implemented starting from the Planning, Implementation and Maintenance Stages, what factors influence the fulfillment of the implementation of the SMKK and then provide a response as an effort to carry out corrective action/improvement. The implementation of SMKK in the Renovation and Expansion Project for the Office Building of the Class 1A Sungguminasa District Court is expected to comply with and refer to the applicable laws and regulations.